2021
DOI: 10.48550/arxiv.2104.12130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal and spectral study of PKS 0208-512 during 2019-20 flare

Rukaiya Khatoon,
Raj Prince,
Zahir Shah
et al.

Abstract: We present the temporal and spectral study of blazar PKS 0208-512, using recent flaring activity from November 2019 to March 2020, as detected by Fermi-LAT, Swift-XRT/UVOT observatories. The source was in a low γ-ray flux state for a decade and started flaring in November 2019, which continues until March 2020. During the activity state, 2-days binned γ-ray lightcurve shows multiple-peaks indicating sub-flares. To understand the possible physical mechanisms behind flux enhancement, a detailed temporal and spec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition to γ-ray data, there exists X-ray, optical, and infrared data for PKS 0208-512, and they have been analyzed in a number of contexts (see e.g. Chatterjee et al 2013;Khatoon et al 2021). It has been suggested that the disk emission is observable when the jet activity is low (Chatterjee et al 2013).…”
Section: Application To Periodic Blazarsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to γ-ray data, there exists X-ray, optical, and infrared data for PKS 0208-512, and they have been analyzed in a number of contexts (see e.g. Chatterjee et al 2013;Khatoon et al 2021). It has been suggested that the disk emission is observable when the jet activity is low (Chatterjee et al 2013).…”
Section: Application To Periodic Blazarsmentioning
confidence: 99%
“…For example, it has recently been noted that PKS 0208-512 has had an increase in γ-ray activity beginning around 2019 (see e.g. Khatoon et al 2021), and the trend in flare amplitudes suggests a lump-like (e.g. 5-orbit) period.…”
Section: Application To Periodic Blazarsmentioning
confidence: 99%